Factors affecting poor breast feathering in modern turkeys - Wylie, Lin M. (The University of Edinburgh, 2000)
Sternal Bursitis (breast blisters) and Focal Ulcerative Dermatitis (breast buttons) cause depressed welfare and are an important source of economic loss in market turkeys. Such lesions are common in modem turkeys and feathers may offer some protection to the breast from environmental challenges. Feather growth is poor in modem compared with traditional turkeys and feathers may be absent over the breast region. This study quantified and compared feather growth in a modem commercial turkey with that in an unrelated traditional turkey and investigated the lack of breast feathers in the large modem bird.

A comparative study found that feather growth had not increased with selection for body weight in the modem turkey and that the growth of breast feathers from the cranial region o f the breast tract appeared to be impaired. Modern birds spent more time resting than traditional turkeys.

Three possible causes of poor breast feathering were examined. First, the reduction in feather growth was an adaptive response to increased heat production resulting from fast growth rates. Second, there was competition between muscle and feathers for essential nutrients such as amino acids. Third, selection for increased breast muscle mass has not resulted in an increase in feather number and was associated with stretching of the skin and poor breast feathering.

Modem turkeys reared at high (26°C) and low (15°C) ambient temperatures showed no differences in feather growth. These turkeys were also fed ad libitum or restricted quantities of feed. Turkeys on restricted feeding showed a general decrease in feather growth apart from the cranial breast feathers that were increased in length.

Nutrition experiments suggested that, in the modem turkey, protein was preferentially partitioned to feather growth and that the amino acids arginine and methionine were used for feather growth in preference to muscle growth. When crude protein concentrations in the diet o f the modem turkey were deficient, feather growth was maintained at the expense of body and particularly breast muscle growth. The impaired development of cranial breast feathers was associated with rapid growth o f the breast muscle in the modern turkey and was not related to a deficiency of specific amino acids.

No increase in feather follicle number and a reduction of the collagen content of breast skin in the modem turkey support the hypothesis that development of the integument has not increased in proportion to body weight

It was concluded that the impaired growth of cranial breast feathers was caused by the rapid growth and sedentary behaviour of the modem turkey resulting in prolonged pressure on the feather tracts of the breast.